PROTECTION OF CAPITAL MARKET RETAIL INVESTOR INTERESTS AGAINST DUAL CLASS VOTING SYSTEMS - Johan, Suwinto; Lie, Gunardi (International Journal of Application on Economics and Business, 2023)
The technology company GoTo has listed its share securities on the Indonesian capital market. GoTo has listed shares with a series or Multiple Voting Shares (MVS) scheme. The Financial Services Authority (OJK) has issued POJK, which regulates MVS. MVS gives rise to shares with voting rights that are different from other shares. This system is known as the dual-class voting system (DCVS). This study aims to discuss how to protect the interests of retail investors who have investments in companies that have MVS. This research uses legal normative. This study concludes that MVS must have a specific validity period, except State-Owned Enterprises (BUMN). The government must own SOEs that influence many people's lives with dual-colored shares. These MVS shares do not have voting rights but still, have the advantage of dividends. The purpose of MVS is for shareholders to protect the company's long-term interests. The government owns Dwiwarna shares intending to safeguard the interests of the national economy. MVS or DCVS affects the long-term running of the company's business to remain appropriate and avoid a hostile takeover.